Images de la femme-auteur dans les paratextes des OEuvres Narratives Feminines Portugaises à L’Age Moderne - Isabel Morujão (Universidade do Porto, 2012)
Paratexts are presentation means for works, authors and genders. They format readers perception about literary texts, taking into consideration the author, the intended public and the work’s merit. Taking as starting point the paratexts that precede the Portuguese feminine narratives published in Portugal from 1555 to late XVIII th century, this paper aims to provide a framework of the feminine editorial visibility and of women’s writer’s image, considering the articulation between gender, production origin and literary function.